Food Safety: Secretome of Lactococcus lactis and Listeria monocytogenes in competition. (International Journal of Health, Animal Science and Food Safety, 2015)
Listeria monocytogenes (LM) is a foodborne pathogen responsible of listeriosis. In the spreading of this pathology, milk and dairy products are key reservoir for this pathogen1. Food processing represents one of the major steps that could be linked to LM growth. Inhibition of LM growth through competition of Lactococcus lactis (LAC) could represent a solution to this problem. Exoproteome of LM and two different strains of Lactic Acid Bacteria in co-culture have been studied in order to highlight mechanisms of bacterial competition useful to improve food safety. Two different strains of LAC and one strain of LM were cultivated in appropriate medium cultures (BHI), also in competition. Filtrated cultures (SECRETOME) were lyophilized and resuspended for proteomics analysis. Shotgun analysis on each secretome was performed on nano UPLC-MS system. Obtained data reveal, during competition, the higher production by LM of moonlighting protein Enolase and Glucose 6 Phosphate isomerase, of Septation ring formation regulator EzrA, involved into cell replication and the lower secretion of Endopeptidase P60. In parallel, L. lactis produced higher amounts of Secreted 45 kDa protein and switched from lantibiotic Nisin A production to Nisin Z production. In competition with LM, LAC strain investigated produce higher amounts of Secreted 45 kDa protein with peptidoglycan lytic activity and the selective secretion of Nisin Z probably to improve lantibiotic solubility in less acidic environment. Next step will be validation of obtained results in dairy products. These results are of interesting to design new strategies of fighting LM as contaminant in food from animal origin.Work supported by Ministry of Health-CCM “Milano EXPO 2015 Project: Garantire la sicurezza alimentare- Valorizzare le produzioni”
Keywords: Foodborne pathogen; bacterial competition; proteomics